2021
DOI: 10.1021/acs.oprd.1c00235
|View full text |Cite
|
Sign up to set email alerts
|

Air-Stable Iron-Based Precatalysts for Suzuki–Miyaura Cross-Coupling Reactions between Alkyl Halides and Aryl Boronic Esters

Abstract: The development of an air-stable iron(III)-based precatalyst for the Suzuki−Miyaura cross-coupling reaction of alkyl halides and unactivated aryl boronic esters is reported. Despite benefits to cost and toxicity, the proclivity of iron(II)-based complexes to undergo deactivation via oxidation or hydrolysis is a limiting factor for their widespread use in cross-coupling reactions compared to palladium-based or nickel-based complexes. The new octahedral iron(III) complex demonstrates long-term stability on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…To highlight the advantage of using an alkoxide base, aryl nucleophiles with base-sensitive functionality were examined. Base-sensitive functionality is often not tolerated for the nucleophilic partner in methods that rely on Grignard reagents or methods involving boron-based nucleophiles activated with alkyl lithium or amide bases. ,, The ester-containing nucleophile 4v and the aryl nitrile 4w were compatible with the iron-catalyzed method and the desired product obtained in 93% and 99% yields, respectively (Scheme B). The base-sensitive functionality was also tolerated on the electrophile, allowing cross-coupling of nitrile ( 4x ) and enolizable ester ( 4y ) containing substrates in 90% and 98% yield, respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To highlight the advantage of using an alkoxide base, aryl nucleophiles with base-sensitive functionality were examined. Base-sensitive functionality is often not tolerated for the nucleophilic partner in methods that rely on Grignard reagents or methods involving boron-based nucleophiles activated with alkyl lithium or amide bases. ,, The ester-containing nucleophile 4v and the aryl nitrile 4w were compatible with the iron-catalyzed method and the desired product obtained in 93% and 99% yields, respectively (Scheme B). The base-sensitive functionality was also tolerated on the electrophile, allowing cross-coupling of nitrile ( 4x ) and enolizable ester ( 4y ) containing substrates in 90% and 98% yield, respectively.…”
mentioning
confidence: 99%
“…A possible pathway of transmetalation is shown in Scheme b, whereby an iron halide intermediate reacts with an aryl boronate to form an iron aryl complex. In contrast, Byers and co-workers have reported that lithium amide boronate nucleophiles were not competent in catalysis, suggesting a potential difference in the mechanism of the transmetalation step …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The current state of the art in iron-catalyzed C­(sp 2 )–C­(sp 3 ) SMC is arguably the catalyst system recently developed by Byers and co-workers, which is the first to allow the direct use of neutral, unactivated arylboronic esters. The Byers catalysts are based on L,X-type N,N ligands and utilize LiNMeEt as the base in benzene solvent (Scheme a) . Unfortunately, the use of a strong lithium amide base that is not currently commercially available and a highly toxic solvent pose significant barriers for utilization of this technology in large-scale applications.…”
Section: New Transformations Enabled By Earth-abundant Metalsmentioning
confidence: 99%
“…The Suzuki–Miyaura cross-coupling reaction of bromocyclobutane ( 96 ) with phenylboronic ester 103 was catalyzed by an air stable iron( iii )-based complex (Fe cat.) to produce 104 in modest yield (31%) 67 (Scheme 48).…”
Section: Cross-coupling Reactions Between Cyclobutyl Halides and Orga...mentioning
confidence: 99%